Analisis Pengaruh Teknologi Augmented Reality (AR) dan User-Generated Content (UGC) pada E-commerce Terhadap Kepercayaan dan Kepuasan Konsumen Generasi Z - Mukhamad Kholil Aswan; Tri Maryani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study focuses on the urgency of the influence of Augmented Reality (AR) Technology and User-Generated Content (UGC) on consumer trust and satisfaction in Generation Z in E-commerce. This study looks at the increasing use of digital platforms among the younger generation, the purpose of this study is to see the influence of AR on trust, the influence of UGC on trust, the influence of AR on consumer satisfaction, the influence of UGC on consumer satisfaction and the influence of trust on consumer satisfaction. This study uses a quantitative approach by collecting data through questionnaires distributed to 400 respondents from the Gen Z population who are active online shoppers. The analysis technique is carried out by first testing the research instrument, namely the reliability and validity test, then testing using Structural Equation Modeling (SEM) with Amos 24. The results of this study provide an explanation that the integration of AR technology in the online shopping experience, as well as the existence of content generated by users can increase the value of Gen Z consumer trust. This study provides valuable insights for the E-commerce industry in designing more effective and efficient marketing strategies that are attractive to Generation Z consumers. Utilizing AR and UGC can create a more interactive shopping experience and trust on E-commerce platforms.